Social Anthropology inside Indigenous Peoples from the perspective of an argenmex anthropologist - Barabas, Alicia (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2022)
This article tries to make a brief comparison between the Social Anthropology carried out in Argentina and México between 1960 and 1990, approximately, with the purpose of showing what  the direction and relevance of the research and studies on indigenous peoples was during those years, as well as to position the ethnographic method within Anthropology.